Micro-capacitor with vertically grown silver nanowires and bismuth ferric oxide composite structures on silicon substrates. (March 2017) - Choi, Daniel; An, Boo Hyun; Mansouri, Mariam; Ali, Dima; Khalil, Malathe; Xu, Ke; Nwoke, Dominic; Park, Jung-Rae; Shankar, Akash; Ryu, Jong Eun
We have designed and demonstrated a complementary metal-oxide-semiconductor compatible process for fabricating high capacitance micro-capacitors based on vertically grown silver nanowires on silicon substrates. Array of silver nanowires with high-aspect ratio were electrochemically grown in the pores of anodized aluminum oxide film, which was pre-formed through anodization of aluminum thin film deposited on titanium/silicon oxide/silicon substrates. High dielectric bismuth ferric oxide layer was electrodeposited to fill the gap between silver nanowires after anodized aluminum oxide film was removed. It was found that the micro-capacitor based on the silver nanowires/bismuth ferric oxide composite film possessed higher capacitance by approximately one order of magnitude from the COMSOL simulation results from the flat Ag thin-film capacitor and the silver nanowire capacitor.